“WE JUST TOOK OUR ‘OPINCI’ OFF, AND ETHNOLOGISTS WANT US TO PUT THEM BACK ON.” THE STATUS OF ETHNOLOGY IN MACEDONIA IN THE SOCIALIST PERIOD (1946-1953) - Ljupco S. Risteski (EtnoAntropoZum, 2020)
The text attempts to bring light to significant events connected to the creation and closure of the academic studies in ethnography and ethnology at the Faculty of Philosophy in Skopje in the early socialist period of 1946 to 1953. The analysis includes archived materials from the archives of the Faculty of Philosophy, and the Ministry of Education of the Socialist Republic of Macedonia. Emphasis has been placed on the socio-political conditions during which the studies were begun and shortly after that closed. The paper notes the social and local political and ideological frameworks for living in the socialistic community. Questions connected to the rise and fall of national ethnology in the Socialist Republic of Macedonia are related to ideological frameworks for how socialism’s dealt with rural life, royalism, backwardness, traditionalism in contrast to urban employment, communism, progress, and modernity.